The Effect of Green Brand Awareness and Green Brand Image on Sustainable Purchase Intention With Green Brand Trust as a Mediation Variable in Cake Products in Yogyakarta - Riyan Indra Wijaya; Albari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of green brand awareness, green brand image, and green brand trust on sustainable purchase intention among Cocoabutter Yogyakarta consumers. The research approach used is a quantitative approach. The population in this study are consumers who have never purchased but have received information. The sampling technique used a non-probability sampling method with a convenience sampling technique. The number of samples in this study was 281 respondents. The research data was obtained through online questionnaires using Google Forms with measurements using a 5-point Likert scale. The research data were analyzed using SmartPLS software version 4.1.1.8 with the Structural Equation Model (SEM) method. The results of the analysis show that green brand awareness has a positive and significant effect on green brand image, green brand awareness has a positive and significant effect on sustainable purchase intention, green brand awareness has a positive and significant effect on green brand trust, green brand image has a positive and significant effect on sustainable purchase intention, green brand image has a positive and significant effect on green brand trust, and green brand trust has a positive and significant effect on sustainable purchase intention among Cocoabutter Yogyakarta consumers.